Amor Deliria Nervosa: The Erasure of Love in Young Adult Dystopian Fiction - Tânia Cerqueira, (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2025)
ABSTRACT: In Lauren Oliver’s Delirium series (2011–2013), love, or amor deliria nervosa, has become the most dangerous disease in the world. Lena, the novel’s protagonist, has been told all her life that love is the deadliest of all deadly things and cannot wait to go through the medical procedure that will cure her of it. Without romantic love, relationships are chosen by the government, which pairs heterosexual couples by considering the results of an evaluation. The erasure of love is present in other young adult (YA) dystopian texts. In Ally Condie’s Matched Trilogy (2010–2012), society bases its decisions on optimal algorithmic calculations, and a person’s forever match is determined by probabilities that exclude love. In Anna Carey’s Eve Series (2011–2013), girls are taught to fear men so that they can be easily manipulated out of romantic relationships and willingly accept becoming breeders for a society decimated by a plague. More insidiously, in Beth Revis’s Across the Universe (2011–2013), the inhabitants of the spaceship are drugged to suppress their emotions. By undertaking an analysis of YA dystopian texts, I examine how love is represented in these future totalitarian societies, and the consequences of its erasure. This article critically engages with frameworks that explore romantic relationships as catalysts for political awakening, highlighting the interconnections between rebellion and sexual awakening. Since love is often represented as undesirable to the regimes that go to great lengths to eradicate it from society, I contend that the experience of love in these narratives is essential for social dreaming.